Green Island - Kwang Hwa Mass Communication ([Taiwan : Kwang Hwaa Mass Communications, 2008)
Sitting just kilometers off the coast of Taiwan, Green Island is a island of mystery. The island's inhabitants believe that whenever they lose their way at sea, it will rise from out of the water like a column of fire and guide them home. Learns the origins of this inhospitable place and see the abundant life that has sprung up here. Peer into the depths of the oceans below and penetrate the forests above. Witness the majesty and splendor that is Green Island
Executive producer, Wang Yuan-tung ; producer, Frank J.K. Chen ; director, Albert Wang ; supervisor, Vanessa Yea-ping Shih ; supervisor producer, William J.T. Yih
DVD Format
Audio available in Chinese, English, French and Spanish, German, Japanese and Russia
Keywords: Natural history -- Taiwan; Natural history -- Oceania